1998
DOI: 10.2527/1998.7641112x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of species raw material source, ash content, and processing temperature on amino acid digestibility of animal by-product meals by cecectomized roosters and ileally cannulated dogs.

Abstract: We conducted experiments to determine amino acid (AA) digestibility of nine animal by-product meals using precision-fed cecectomized roosters and ileally cannulated dogs. The products initially evaluated in roosters were meat and bone meals (MBM) containing 24 or 34% ash, poultry by-product meals (PBP) containing 7 or 16% ash, lamb meals (LM) containing 15 or 24% ash, a LM analog containing a mixture of LM and turkey meal, and two MBM processed at either a low or high temperature. The MBM and PBP differing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
92
2
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 29 publications
16
92
2
5
Order By: Relevance
“…The differences in the composition of the feedstuffs can also interfere in the digestibility coefficients of the nutrients, e.g., in the case of the meat and bone meal, in which there is no standardization during the processing to its obtainment, thus leading to variations mainly in the content of mineral matter and protein; Johnson et al (1998) elevated contents of ash cause decrease in the amount of protein, decreasing the levels of essential amino acids per unit of protein, without affecting its quality. The pearl millet presented different true digestibility coefficients of essential amino acids from the two varieties assessed by Rodrigues et al (2001a), like Rostagno et al (2005), who showed different values, except for arginine, which presented value similar to that of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in the composition of the feedstuffs can also interfere in the digestibility coefficients of the nutrients, e.g., in the case of the meat and bone meal, in which there is no standardization during the processing to its obtainment, thus leading to variations mainly in the content of mineral matter and protein; Johnson et al (1998) elevated contents of ash cause decrease in the amount of protein, decreasing the levels of essential amino acids per unit of protein, without affecting its quality. The pearl millet presented different true digestibility coefficients of essential amino acids from the two varieties assessed by Rodrigues et al (2001a), like Rostagno et al (2005), who showed different values, except for arginine, which presented value similar to that of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is instructive that these studies generally report that ileal digestibility of MBM is reduced by cooking. Among dogs, for example, Johnson et al (1998) found the ileal digestibility of MBM to be inversely correlated with processing temperature. Among roosters, Johns et al (1987) found negative effects of cooking time on ileal digestibility of MBM heated at 150°C for 1, 1.5, 3, 4, and 5 hours.…”
Section: Increased Digestibilitymentioning
confidence: 99%
“…O processamento da farinhas animais na graxaria, especificamente a temperatura, a pressão e o tempo empregados, também pode comprometer a qualidade do produto, seja carbonizando matéria orgânica, diminuindo a digestibilidade total, seja tornando aminoácidos específi-cos indisponíveis. Essas variações têm reflexo direto na qualidade protéica destes ingredientes, podendo ocasionar grandes diferenças entre batidas e principalmente entre fornecedores destes subprodutos (Parsons et al,1997;Shirley & Parsons, 2000;Johnson et al, 1998). Johnson et al (1998) estudaram a digestibilidade de aminoácidos da farinha de carne e ossos processada em alta (145 o C) ou baixa temperatura (110 o C) e encontraram, respectivamente, coeficientes de digestibilidade aparente médios de 79,2 e 86,4% para os aminoácidos essenciais e de 75,2 e 84% para aminoácidos totais, demonstrando a grande influência do processamento sobre a digestibilidade.…”
Section: A B C Means Of the Same Nutrient Without A Common Letter Dunclassified
“…Como a origem e o processamento dos ingredientes são fatores determinantes para sua qualidade e digestibilidade (Johnson et al, 1998), a escassez de informações sobre o aproveitamento destas matérias-primas, especialmente as de origem animal, dificulta a formulação de dietas para cães no Brasil, pois os nutricionistas têm acesso apenas a dados de estudos internacionais.…”
Section: Introductionunclassified